Comparative study on the effects of chelated or inorganic manganese in diets containing tricalcium phosphate and phytate on the growth performance and physiological responses of turbot Scophthalmus maximus. (4th November 2014) - Ma, R.; Hou, H.; Mai, K.; Bharadwaj, A.S.; Ji, F.; Zhang, W.
Abstract: A growth trial was conducted to evaluate the effects of chelated (Mintrex ™ Mn, Mn‐M) or inorganic (MnSO4 ·H2 O, Mn‐S) manganese (Mn) on growth, feed utilization, tissue Mn deposition and liver superoxide dismutase (SOD) activity in turbot Scophthalmus maximus . A semi‐purified basal diet was formulated to be deficient in Mn (3.7 mg kg −1 ) and contained tricalcium phosphate and sodium phytate at levels of 20 and 5 g kg −1, respectively. Ten other diets were made by adding five levels (5, 10, 20, 35 and 55 mg Mn kg −1 diet) of either the Mn‐M or Mn‐S to the basal diet, respectively. The 11 experimental diets were fed to groups of turbot (mean initial weight: 4.6 g) for 8 weeks. Results showed that the specific growth rate (SGR), feed intake, whole body Mn/vertebra Mn concentration and Mn‐SOD activity in liver were significantly improved by Mn supplementation ( P  <   0.05). On the basis of SGR, vertebra Mn concentration or liver Mn‐SOD activity data, dietary Mn requirement was estimated to be 10.5, 46.3 or 12.9 mg kg −1 for turbot fed Mn‐S, and the same was estimated to be 7.6, 43.0 or 22.5 mg kg −1 for turbot fed Mn‐M, respectively. There was no significant difference in growth, feed intake, whole body Mn concentration or vertebra Mn concentration between the two dietary Mn sources ( P  >   0.05).